Behring Sea Arbitration. Report of the Behring Sea Commission, and report of British Commissioners of June 21, 1892. With five maps and diagrams, and appendices . - Bering Sea Commission.; Great Britain. Bering Sea Commissioners.; Bering Sea Tribunal of Arbitration. (London, Printed for H.M. Stationery Off., by Harrison and Sons, 1893)
Mode of access: Internet.